ECOINOVATION PRACTICES AND THE SOCIOTECHNICAL TRANSITION IN CIVIL CONSTRUCTION: A CASE STUDY IN BRAZIL - Denes dos Santos, Danielle; Adélia Becker, Cristiane (Organizações e Sustentabilidade, 2022)
The world is sensitive to unbridled consumption that impacts on sustainability. Eco-innovation has been shown to be an approach that seeks to understand sustainable innovations as an alternative to the economic development of societies. The main contribution of this paper is to describe how the system of eco innovation practices was developed in the process of socio-technical transition to sustainability in a construction company. From a qualitative approach we describe how eco-innovation practices are developed in a construction company with socio-technical theory and social practice theory. This analysis allowed us to understand how eco-innovation practices are developed, considering points that delay or stimulate the transition to sustainability. The results showed some intersections with niche, regime and landscape, many of them stimulating sustainability and others slowing down. We also included an amplification of the theory by showing that the intersections that stimulate are more organized in practices, and those that delay find strong barriers in the regime.